Implementation of Integrated Action to Prevent Stunting Program in Pandeglang Regency - Ismiati Kasum, Femy; Yeni Widyastuti; Ato’uallah (Epistemik Press, 2025)
The eradication of Stunting is one form of the Government of Indonesia to carry out the Sustainable Development Goals or often known as Sustainable Development Goals (SGD's) initiated by the United Nations (UN). Pandeglang Regency is one of the districts in Banten Province with the highest number of Stunting children. In order to achieve more decent human welfare, Pandeglang Regency Government tries to reduce the number of Stunting children in Pandeglang Regency through the Integration Program for Action to Prevent Stunting accompanied by other programs related to fulfilling child nutrition to reach the level of age maturity. This study aims to determine how the implementation of the Stunting Prevention Action Integration Program in Pandeglang Regency with the research method used is descriptive qualitative. The collection techniques used are primary data with interviews, observations, and documentation while the secondary data techniques used are documents and other secondary data sources. The results showed that the Action Program to Prevent Stunting in Pandeglang Regency has almost succeeded because only one variable has not met the requirements as a policy that almost achieves its goals.